Impacto del orden fraccional sobre la respuesta en el tiempo de convertidores DC-DC con capacitores fraccionales - López Lezama, Jesús María; Betancur Herrera, David Esteban; Cano, Juan Bernardo; Muñoz Galeano, Nicolás (Scientia et Technica, 2020)
This paper analyses the impact of fractional orders of derivatives over the response of DC-DC converters which includes fractional capacitors and their parasitic losses for a more realistic approximation of the converter. A fractional model is proposed and is applied for a Boost DC-DC with a fractional capacitor in its DC bus. The fractional model is obtained using Kirchhoff laws and applying the conventional switching model. Then, the resulting set of fractional differential equations is in the Caputo’s sense and was solved using Wavelets method. Solutions were appropriately shown using 3D representations, varying the duty cycle and the fractional order to determine the behaviour of the fractional capacitor voltage, inductor current and output voltage. Ripples and steady state values were determined. Results show high dependence of the fractional order in the variables related to the voltage in the fractional capacitor. With respect to the current, results show that the fractional order does not significantly affect its steady state and ripple.